PENGARUH STIMULASI ORANG TUA TERHADAP PERKEMBANGAN BAHASA ANAK USIA TODDLER - Enggal Sari Maduratna (NHM PRESS, 2019)
Language development is the ability to respond to sounds, follow orders and speak spontaneously. Based on a preliminary study in Buluh Socah Polindes from 10 children aged toddler, found 60% of children experience delays in language development caused by lack of stimulation. The purpose of this study to influence of relationship stimulation with the development of toddler children language. The research design used analytic correlation with cross sectional approach. Its population is all toddler age children in Work Area of Polindes Banyuanyar districts Sampang as many as 33 people, total samples are 30 people. Samples were taken by proportionate stratified random sampling method. The independent variables are stimulation, while the dependent variable is language development. Data collection using questionnaires and DDST II sheets were processed using Spearmen Rank statistical test. The result showed that parents who provide good stimulation have all the children with normal language development (100%). Based on Spearmen Rank statistical test with ρ (0.00) <α (0.05) so H_1 is accepted, meaning that there was relationship of stimulation and language development of toddler age children. Based on the result of the study is expected parents are able to interact with children and teach children to speak clearly and easy to understand, so it help children language development optimally. It is suggested that further researchers use more samples to obtain better results